Quality improvement exercises in Inflammatory Bowel Disease (IBD) services: A scoping review. - Katie Ridsdale; Kajal Khurana; Azizat Temidayo Taslim; Jessica K Robinson; Faith Solanke; Wei Shao Tung; Elena Sheldon; Daniel Hind; Alan J Lobo (PLoS ONE)
Objective Quality Improvement initiatives aim to improve care in Inflammatory Bowel Disease (IBD). These address a range of aspects of care including adherence to published guidelines. The objectives of this review were to document the scope and quality of published quality improvement initiatives in IBD, highlight successful interventions and the outcomes achieved. Design/method We searched MEDLINE, EMBASE, CINAHL and Web of Science. Two reviewers independently screened and extracted data. We included peer reviewed articles or conference proceedings reporting initiatives intended to improve the quality of IBD care, with both baseline and prospectively collected follow-up data. Initiatives were categorised based on problems, interventions and outcomes. We used the Quality Improvement Minimum Quality Criteria Set instrument to appraise articles. We mapped the focus of the articles to the six domains of the IBD standards. Results 100 studies were identified (35 full text; 65 conference abstracts). Many focused on vaccination, medication, screening, or meeting multiple quality measures. Common interventions included provider education, the development of new service protocols, or enhancements to the electronic medical records. Studies principally focused on areas covered by the IBD standards 'ongoing care' and 'the IBD service', with less focus on standards 'pre-diagnosis', 'newly diagnosed', 'flare management', 'surgery' or 'inpatient care'. Conclusion Good quality evidence exists on approaches to improve the quality of a narrow range of IBD service functions, but there are many topic areas with little or no published quality improvement initiatives. We highlight successful quality improvement interventions and offer recommendations to improve reporting of future studies.